Ang Konsepto ng Planetisasyon ni Teilhard de Chardin: Isang Pagsusumubok Bigkasin ang Meron - Strebel, Wilhelm P.J. (Archīum Ateneo, 2015)
In his book Pambungad sa Metapisika, Roque J. Ferriols, SJ, stresses that metaphysics is a practicum. Metaphysics makes one aware of reality, and this awareness drives the person to affirm, respect, and work and move in accord to and within it. This response to reality is what Ferriols calls “pagbigkas sa meron.” Ferriols also devotes a chapter of his book to the thought of the French paleontologist, Pierre Teilhard de Chardin, SJ. The paper explores how this understanding of Teilhard’s thought leads to the practicum identified above as “pagbigkas sa meron.” The paper begins with an exposition of the key concepts found in Ferriols’s book relevant to Teilhard’s “planetisation,” or the furling back upon itself of a “bundle” of potential species around the surface of the earth, a movement that could lead to the destruction of humankind itself but which could also occasion unity or what he called the “brotherhood of persons.” Then it argues that Teilhard’s concept of planetisation implies an act of “pagbigkas sa meron.”